Playing for dollars : labor relations and the sports business - Staudohar, Paul D. (Cornell paperbacks., 1996)
Fans of professional sports have been forced to pay attention to labor relations in the last five years. The 1994-1995 season reminded baseball enthusiasts that a players' strike can mean something more than a swing and a miss, and the fans of other sports have experienced similar frustrations. In Playing for Dollars, Paul D. Staudohar analyzes the business dimension of sports with a timely assessment of the interactions among labor, management, and government in baseball, football, basketball, and hockey.